القيمة الدلالية للصوت في روايات علي الجارم التأريخية - علي, گەشە عبدالله; كريم, هيوا عبدالله (Sulaimani Journal for Humanities, 2018)
Sounds have undoubtedly a significant impact in determining the semantics of verbal structures and directing them. They are what make words to have their reporting, expressive and communicative dimensions. They also provide meaning by combining with each other, which in turn provide means to express different feelings and emotions. Each word maintains a different sound form another, which is selected according to the characteristics of their suggestive and semantic sounds. And, this is achieved in an appropriate contextfor the perception of the recipient. Based on the importance of the sound effect in the production of semantics, this research aims to study the acoustic structure of words in the historical novels ofAli Jaram, which are distinguished by the strength of literary style and poetic language. The research focuses on reading the texts of novels in the hope of finding of the accurate meaning of the words and exploring the sound values and their effects onproper semantics. 963 In order to achieve the desired goal, we organized a research based on a descriptive analytical approach, consisting of an introduction, a theoretical approach, two studies and a conclusion. In the introduction, we talk briefly about the concept of semantic of sounds, the elements of its realization, and the scientists' understanding of the strong connection between sound and semantics. While the first study deals with the significance of semantic value of sounds on words that are similar in meaning (synonyms), the second study centers on the significance of the semantic value of sounds on words that have contrasting meanings (antonyms). In both studies, the research islimited to a selection of words. In the conclusion, we present the most important results we have reached. In this work, we have relied on a variety of sources and references, such as dictionaries and language and semantic books.